2016
DOI: 10.18632/oncotarget.8514
|View full text |Cite
|
Sign up to set email alerts
|

Direct repression of the oncogene CDK4 by the tumor suppressor miR-486-5p in non-small cell lung cancer

Abstract: MicroRNAs are a class of non-coding single-stranded RNA, 20-23 nucleotide in length, which can be involved in the regulation of gene expression. Through binding with 3'-untranslated regions (3'-UTR), microRNAs can cause degradation of target mRNAs or inhibition of translation, and thus regulating the expression of genes at the post-transcriptional level. In this study, we found that miR-486-5p was significantly downregulated in non-small cell lung cancer (NSCLC) tissues and cell lines, suggesting that miR-486-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…1A). Although miR-486-5p down-regulation and its effects in promoting lung carcinogenesis have been previously reported [3,810], the mechanism of repression is unknown. MicroRNAome analysis of NSCLC cell lines treated with vehicle or DAC as described [33] showed that DAC treatment increased miR-486-5p expression in 5/10 cell lines with lowest expression by 2 to 8-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Although miR-486-5p down-regulation and its effects in promoting lung carcinogenesis have been previously reported [3,810], the mechanism of repression is unknown. MicroRNAome analysis of NSCLC cell lines treated with vehicle or DAC as described [33] showed that DAC treatment increased miR-486-5p expression in 5/10 cell lines with lowest expression by 2 to 8-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, abnormal repression of this miR in cancer provides a growth advantage by enhancing the tumor-promoting properties of its targets. Among miR-486-5p target oncogenes that get activated following its downregulation in lung cancer include: CDK4, which promote cell cycle progression [3], ARHGAP5, which regulates cellular adhesion, motility, and polarity to promote cell migration and invasion [10], the growth promoting IGF signaling genes IGF1, IGF1R, and PIK3R1 [9], and the proto-oncogene serine/threonine kinase PIM-1 [8]. The tumor-suppressor role of miR-486-5p is also demonstrated in other cancers where it targets PIM-1 in breast cancer [43], SNAI1 in prostate cancer [44], and CLDN10, CITRON, and PIK3R1 in HCC [45,46] [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that aberrant miR-486-5p expression could affect the occurrence and progression of many diseases [26,27]. Notably, the effect of miR-486-5p is controversial because it was found to serve as a suppressor or oncogene in studies [28,29]. In addition, we saw that miR-486-5p's function had not been explored in COPD.…”
Section: Discussionmentioning
confidence: 91%
“…We found that mir-486 had tumor suppressing effect in LUAD, and many previous studies support this conclusion. Yu et al found that miR-486 inhibits cell proliferation and invasion through repressing GAB2 in LUAD [40], and miR-486played an anti-tumor function by targeting CDK4 in LUAD [41].…”
Section: Discussionmentioning
confidence: 99%